Analisa daya dukung sub das Batang Kumu Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Rudi Hasmadan; Zulkifli Zulkifli; Imam Suprayogi (Pelantar Press, 2019)
The purpose of the research is to analyze the carrying capacity of Sub watershed Batang Kumu in existing conditions that are useful as a direction for the management of Sub watershed Batang Kumu to maintain sustainability. The method of approach used using policy instruments from the Ministry of Environment and Forestry (LHK) of the Republic of Indonesia which has published regulation of the Minister of Forestry of the Republic of Indonesia no.61 /Menhut II/ 2014 on monitoring and evaluation of watershed management with assessment of criteria covering land, water system, socioeconomic, value of building investment and utilization of regional space. The data used for the research includes land use data, high water level and water quality sample test results sourced from BP-DAS Indragiri Rokan, rainfall data sourced from The River Regional Basin (BWS) of Sumatra III, socioeconomic and population data from the Central Bureau of Statistics (BPS) of Rokan Hulu Regency as well as building investment value data sourced from the Public Work Office of Rokan Hulu Regency. The results of the research stated the total carrying capacity value of Sub watershed Batang Kumu is 117.5. The condition of support capacity of Sub watershed Batang Kumu Sub-District Rambah Hilir Rokan Hulu regency is in the category of bad or in other words Sub watershed Batang Kumu that deserves to maintain its supporting capacity where socioeconomic and institutional assets / value and investment of buildings function as they should. While land conditions, water systems and regional development policies are performance parameters of Sub watershed Batang Kumu which has an influence in increasing the risk of ineligion to the sustainability of watershed ecosystems especially the percentage of critical land, the percentage of vegetation closures and erosion index that shows a very high classification level followed by sub criteria of flooding with high classification and protected areas with very poor classification